Literature Review: How Competency, Auditor Professionalism, and Integrity Influence Internal Audit Quality - Asri Ady Bakri (Penelitian dan Pengembangan Ilmu, 2024)
Previous research is very important in a research or scientific article. Relevant research functions to strengthen theories and phenomena of relationships or influences between variables. This article reviews. Factors that influence Internal Audit Quality, namely: Competence, Auditor Professionalism and Integrity. The purpose of writing this article is to determine the influence of Competency, Auditor Professionalism and Integrity on Internal Audit Quality. Article results are: Competency, Auditor Professionalism and Integrity influences Internal Audit Quality.